The protective effect of hydroalcoholic Citrus aurantifolia peel extract against doxorubicin-induced nephrotoxicity - Ni Made Dwi Sandhiutami; Yesi Desmiaty; Putu Diah Utari Pitaloka; Salsabila Salsabila (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Doxorubicin chemotherapy is a widely used treatment for various cancers, including breast, ovarian, and uterine cancers, among others. However, long-term use can cause nephrotoxicity side effects. Some citrus flavonoids have demonstrated nephroprotective activity; therefore, this study aimed to test the nephroprotective effectiveness of Citrus aurantifolia peel extract in protecting and reducing kidney damage caused by doxorubicin. Experimental approach: Citrus aurantifolia peel was dried, ground, and extracted by ultrasonication (70% ethanol), then the extract was dried. Twenty-five female Sprague-Dawley rats were divided into 5 groups including the normal group (control), positive control (doxorubicin) group receiving doxorubicin at the repeated intraperitoneal (i.p.) dose of 4 mg/kg/day on days 2, 6, 10, and 14, and treatment groups receiving Citrus aurantifolia peel extract (CPE) with the doses of 100, 200, and 400 mg/kg/day orally for 14 days, and doxorubicin (4 mg/kg/day, i.p.) on days 2, 6, 10 and 14. On day 15, the rats were euthanized for the measurements of MDA, superoxide dismutase (SOD), catalase, kidney function (measuring blood urea nitrogen (BUN), creatinine, albumin serum levels), and renal histopathology. Findings/Results: The CPE yield was 16.13%. CPE could significantly reduce the levels of MDA, and increase SOD and catalase activities compared with the doxorubicin-induced nephrotoxic model. CPE could increase renal function by reducing BUN and creatinine levels, increasing albumin, and improving the histopathology of the kidney. Conclusion and implications: CPE has a potential effect as nephroprotective against doxorubicin-induced toxicity in renal through antioxidant capacities and increased renal function.